Social Company by a Receptive Mating Partner Facilitates Fear Extinction - Gao, Feng; Huang, Jie; Guan, Yan-Fei; Huang, Guo-Bin; Li, Wen-Jing; He, Xi-Yi; Qiu, Zi-Cong; Zhang, Yun-Long; Zhao, Shen-Ting; Li, Jianhua; Xuan, Aiguo; Sun, Xiang-Dong (Frontiers in Neuroscience, 2020)
Fear extinction remains an unresolved challenge for behavioral exposure therapy in patients with post-traumatic stress disorder. Previous reports have suggested that social support from either familiar or unfamiliar same-sex partners is beneficial to attenuating fear response during fear extinction and renewal. Despite that, few studies have examined the effects of social support in advance on fear extinction and/or retrieval. It is also not clear whether social company by a receptive mating partner in advance facilitates fear extinction. In the present study, we address these questions by introducing a co-housing method, where fear-conditioned male mice are co-housed with or without a receptive mating partner prior to fear extinction. We found that while co-housing with an ovariectomized female mouse showed little effect on fear extinction or retrieval, social company by a receptive mating partner in advance dramatically facilitates fear extinction. In addition, the number of cFos-positive neurons in the basolateral amygdala (BLA) was also found reduced in male mice accompanied with receptive mating partner in response to fear extinction and retrieval, indicating diminished neuronal activation. Electrophysiological studies further showed that the excitability of excitatory neurons in BLA is decreased, which is probably due to the attenuated basal level of excitatory synaptic transmission. Together, our observations demonstrate an effect of social company by a receptive mating partner on facilitating fear extinction and afford a possible cellular mechanism.